Anglicanorum Coetibus: Modifications of the Complementary Norms - Ecclesia Catholica Sacra Congregatio pro Doctrina Fidei Archivio (2013)
In a letter to the Ordinary of the Anlgican Ordinariate for the Chair of St. Peter in the United States, the Prefect of the Congregation for the Doctrine of the Faith communicated modifications to Aticle 1.4 and Complementary Norm 5.1 of the Apostolic Constitution Anglicorum coetibus. The modification addresses a particular question of who is eligible for membership in the Ordinariate. The changes were confirmed by Pope Franics. The Prefect's letter follows.
Keywords: Church of England; Gesetzgebung; Norm